Development of Guided Inquiry Based Learning Modules to Improve Environmental Attitude and Hight Order Thinking Skills (Universitas Negeri Semarang, 2021)
Education as the main foundation for individuals to develop their abilities. This research includes research and development (R&D). This Research aims to find out how the validity and effectiveness of guided inquiry-based learning modules to improve environmental attitudes and HOTS (Higher Order Thinking Skills) of students. This research used 32 students as sample. Data analysis in this study used descriptive qualitative analysis techniques. The implementation of this learning module shows an increase related to the attitude of caring for the environment and HOTS of students. The benefits of this research for educators are to provide a reference to learning models that are effective in increasing environmental attitudes of students and HOTS of students. The conclusions in this research are guided inquiry-based learning modules in environmental pollution lesson is valid and effectively used to increase environmental attitudes of students and HOTS of students.